Advancement of fluorescent aminopeptidase probes for rapid cancer detection–current uses and neurosurgical applications - Shimizu, Takenori; Tanaka, Shota; Kitagawa, Yosuke; Sakaguchi, Yusuke; Kamiya, Mako; Takayanagi, Shunsaku; Takami, Hirokazu; Urano, Yasuteru; Saito, Nobuhito (Frontiers in Surgery, 2024)
Surgical resection is considered for most brain tumors to obtain tissue diagnosis and to eradicate or debulk the tumor. Glioma, the most common primary malignant brain tumor, generally has a poor prognosis despite the multidisciplinary treatments with radical resection and chemoradiotherapy. Surgical resection of glioma is often complicated by the obscure border between the tumor and the adjacent brain tissues and by the tumor's infiltration into the eloquent brain. 5-Aminolevulinic acid is frequently used for tumor visualization, as it exhibits high fluorescence in high-grade glioma. Here, we provide an overview of the fluorescent probes currently used for brain tumors, as well as those under development for other cancers, including HMRG-based probes, 2MeSiR-based probes, and other aminopeptidase probes. We describe our recently developed HMRG-based probes in brain tumors, such as PR-HMRG, combined with the existing diagnosis approach. These probes are remarkably effective for cancer cell recognition. Thus, they can be potentially integrated into surgical treatment for intraoperative detection of cancers.